2017
DOI: 10.1534/genetics.117.200568
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of the Regulation of Development and Metabolism by Neuronal eIF2α Phosphorylation in Caenorhabditis elegans

Abstract: Cell-nonautonomous effects of signaling in the nervous system of animals can influence diverse aspects of organismal physiology. We previously showed that phosphorylation of Ser49 of the a-subunit of eukaryotic translation initiation factor 2 (eIF2a) in two chemosensory neurons by PEK-1/PERK promotes entry of Caenorhabditis elegans into dauer diapause. Here, we identified and characterized the molecular determinants that confer sensitivity to effects of neuronal eIF2a phosphorylation on development and physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Meanwhile, ER stress-mediated dauer diapause is also regulated by other sensory neurons, such as the ASI neurons [108]. It has been suggested that the mutated DAF-28 peptide in the daf-28 ( sa191 ) mutant strain triggers ER stress and activation of the unfolded protein response (UPR) to induce constitutive dauer entry [108,109,110,111].…”
Section: Implications Of Ascr Pheromone Metabolism In Neuroprotectionmentioning
confidence: 99%
“…Meanwhile, ER stress-mediated dauer diapause is also regulated by other sensory neurons, such as the ASI neurons [108]. It has been suggested that the mutated DAF-28 peptide in the daf-28 ( sa191 ) mutant strain triggers ER stress and activation of the unfolded protein response (UPR) to induce constitutive dauer entry [108,109,110,111].…”
Section: Implications Of Ascr Pheromone Metabolism In Neuroprotectionmentioning
confidence: 99%
“…Ã indicates significant enrichment (P , 0.05; hypergeometric enrichment test). phosph-eIF2a, a marker of cellular stress (Kim et al 2018;Kulalert et al 2017;Taniuchi et al 2016;Pakos-Zebrucka et al 2016). This was indeed the case, and excess 5-HT caused a time-dependent increase in the levels of phosphorylated eIFa ( Figure 5D).…”
Section: Resultsmentioning
confidence: 54%
“…We previously reported the results of a genetic screen for suppressors of the dauer-constitutive (Daf-c) phenotype of the daf-28(sa191) mutant (Kulalert et al 2017). Incomplete suppression of the Daf-c phenotype of the daf-28(sa191) mutant by daf-3 and daf-16 mutations (Malone, Inoue and Thomas 1996; Li, Kennedy and Ruvkun 2003; Kulalert and Kim 2013) suggested that genetic suppressors of daf-28(sa191) might uncover additional novel pathways functioning in parallel to established signaling pathways activating the dauer developmental decision.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, recent studies have shown a role of Rictor/TORC2 and CaMKI in regulating expression of TGF-ligand and insulin-like proteins in response to food signals in dauer entry (Neal et al 2015;O'Donnell et al 2018). We previously described a genetic strategy to identify novel genes involved in dauer formation by undertaking a screen for suppressors of the daf-28(sa191) mutation (Kulalert and Kim 2013; Kulalert et al 2017), which confers constitutive entry into dauer diapause (Malone, Inoue and Thomas 1996;Li, Kennedy and Ruvkun 2003). Here, we have identified and characterized a c-Jun N-terminal Kinase (JNK)-like mitogen-activated protein kinase (MAPK) KGB-1 pathway that functions in the sensory neurons to promote dauer formation.…”
Section: Introductionmentioning
confidence: 99%